DAMPAK PERKEBUNAN KELAPA SAWIT TERHADAP KEANEKARAGAMAN SPESIES TUMBUHAN TROPIKA (STUDI KASUS : PROVINSI RIAU) - Nahlunnisa, Hafizah; Santosa, Yanto; Zuhud, Efrizal AM (Fakultas Kehutanan Universitas Lancang Kuning, 2017)
Oil palm expansion that occurred in Indonesia become the concern today. The expansion of oil palm plantations is a major contribution to the national economy. However oil palm plantations is claimed as the cause of the destruction of primary forests and reduce the diversity of plant species. Therefore, research is needed to explore the history of land cover of oil palm plantations and knowing the divers ity of plant species before and after the oil palm plantations. The study was conducted in March-April 2016 in 6 companies in Riau province. The data collected by the analysis of Landsat imagery to see the condition of land cover prior to their oil palm plantations. In addition, analysis of vegetation in 2-3 plots on land cover before and after the oil palm plantations. The land cover were observed after the oil palm plantations that HCV suspected area as an area that has a high diversity of plant species in oil palm plantations. Analysis of landsat satelite indicated that the history of land cover oil palm plantations is come from secondary forest (19.88%), rubber plantations (59.26%), open land (19.87%), and mixed agriculture (0.99%). The highest diversity of plant that is in HCV which forest areas form . The results showed that the number of plant species was decreased about 60.56-93.33% in the three companies, while the other three companies does not have change the number of plant species. The company did not change the diversity of plant species are those with HCV area in the form of secondary forest that had existed before the oil palm plantations. Thus, there was no history of land cover palm oil from primary forests, and then to the impact of oil palm plantations on plant species diversity was decreased significantly.